Geometric Modeling of ThreeDimensional Space and Body - Yadgarov Uktam Tursinovich (Genius Journals, 2022)
The article considers a geometric body with a figure as an interconnected set of points limited in space in a certain way. Here, when moving a geometric body in space, there is no change in the relative position of its elements.
Keywords: Space; parallel variable; family of lines; spatial curve